2021
DOI: 10.1186/s12904-021-00866-4
|View full text |Cite
|
Sign up to set email alerts
|

Home care nurses more positive about the palliative care that is provided and their own competence than hospital nurses: a nationwide survey

Abstract: Background People often prefer to stay at home until the end of life, but hospital admissions are quite common. In previous research bereaved relatives were found to be less positive about palliative care in hospital. However, it was not known how the content and quality of palliative care differ between home care and hospitals from the perspectives of hospital nurses and home care nurses and how palliative care in these settings could be improved. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Second, previous research indicated that a higher percentage of home-visit nurses stated that they provided care in the physical and psychological domains and discussed EOL decisions with patients than hospital nurses ( Joren et al, 2021 ). These results may support our findings that home-visit nurses assess patients’ physical and mental care needs in conjunction with determining the timing of EOL discussions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, previous research indicated that a higher percentage of home-visit nurses stated that they provided care in the physical and psychological domains and discussed EOL decisions with patients than hospital nurses ( Joren et al, 2021 ). These results may support our findings that home-visit nurses assess patients’ physical and mental care needs in conjunction with determining the timing of EOL discussions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been pointed out that although smaller percentages of nurses in both home care and hospitals provided care in the social and spiritual care domains, relatively more home-visit nurses provided care in these domains than hospital nurses ( Joren et al., 2021 ). This was similar to our findings that home-visit nurses paid attention to patients’ existential distress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data sources that were used were: A questionnaire administered via email to professionals at the beginning (pre‐test) and end (post‐test) of the implementation period. The questionnaire items were based on a previously validated questionnaire on experiences with palliative care (Joren et al, 2021). The questionnaires were completed fully by 299 professionals at baseline (response 45.2%) and 250 professionals at the end of the intervention period (response 35.1%). Group interviews conducted at the end of the intervention period (YDM, ADV), using a topic list.…”
Section: Methodsmentioning
confidence: 99%